Epigenetics and immune cells in medulloblastoma - Gorini, Francesca; Miceli, Marco; de Antonellis, Pasqualino; Amente, Stefano; Zollo, Massimo; Ferrucci, Veronica (Frontiers in Genetics, 2023)
Medulloblastoma (MB) is a highly malignant childhood tumor of the cerebellum. Transcriptional and epigenetic signatures have classified MB into four molecular subgroups, further stratified into biologically different subtypes with distinct somatic copy-number aberrations, driver genes, epigenetic alterations, activated pathways, and clinical outcomes. The brain tumor microenvironment (BTME) is of importance to regulate a complex network of cells, including immune cells, involved in cancer progression in brain malignancies. MB was considered with a “cold” immunophenotype due to the low influx of immune cells across the blood brain barrier (BBB). Recently, this assumption has been reconsidered because of the identification of infiltrating immune cells showing immunosuppressive phenotypes in the BTME of MB tumors. Here, we are providing a comprehensive overview of the current status of epigenetics alterations occurring during cancer progression with a description of the genomic landscape of MB by focusing on immune cells within the BTME. We further describe how new immunotherapeutic approaches could be used to manage the concurring epigenetic machinery within the immunosuppressive cells within the BTME in MB. In conclusion, the modulation of these molecular genetic complexes in BTME during cancer progression might enhance the therapeutic benefit, thus firing new weapons to fight MB.